Phenomenological descriptions of alcohol and substance use in literature - Aksoy, Dilek (Journal of Dependence, 2022)
Objective: Alcohol and substance use, which has a history as long as human history in the narratives in which human experiences are expressed literary, has also been one of the interesting experiences written by the authors in their works. The aim of this study is to examine the phenomenological descriptions in the texts in which the alcohol and substance experience is indirectly presented. Method: In the research, first of all, the literature information about the appearance of alcohol and substance use in literature, what phenomenological description means and how literary narratives can be positioned in phenomenological perspective, framed according to the aim of the study, is presented. Afterwards, in the study, De Quincey’s Confessions of an English Opium-Eater, Baudelaire’s La Paradise Artificials, London’s John Barleycorn: Alcoholic Memoirs, Svevo’s Generous Wine, Bulgakov’s Morphine, Simmel’s To the Bitter End and Benjamin’s On Hashish excerpts have been taken from their works. In order to draw attention to the manifestations of alcohol and substance use in literary works, themes were created according to Colaizzi’s phenomenological analysis strategy from the phenomenological descriptions; descriptions containing these themes were also categorized and discussed under the sub-headings of whiskey, wine, cannabis, opium, morphine and cocaine according to the type of substances. Results: As a result of the analysis of phenomenological descriptions, the themes related to alcohol and substance use in literary works were the reasons for alcohol/substance use, experiences under the influence of alcohol/substance, the meanings attributed to alcohol/substance, and the desire to end alcohol/substance use. Conclusion: It is thought that we look at these expressions, which are in the narration style of the participants in Alcoholics Anonymous meetings, with Husserl’s phenomenological approach, leaving aside our current thoughts about alcohol and substance use and addiction and presenting a functional approach in understanding how this experience appears to the experiencing subject.